The actual and ideal indoor soundscape for work, relaxation, physical and sexual activity at home: A case study during the COVID-19 lockdown in London - Torresin, Simone; Ratcliffe, Eleanor; Aletta, Francesco; Albatici, Rossano; Babich, Francesco; Oberman, Tin; Kang, Jian (Frontiers in Psychology, 2022)
The period of home confinement during the COVID-19 pandemic made the importance of a high-quality surrounding environment even more evident than before. Several studies have been carried out to assess the (negative) impacts of noise on annoyance, particularly whilst working from home (WFH). The present study takes a step further by (1) investigating the positive and negative impacts of the “actual” acoustic environment on a range of activities, i.e., WFH, relaxation, physical, and sexual activities, and (2) identifying the characteristics of an “ideal” indoor soundscape. The study is based on the qualitative analysis of verbal descriptions collected from open-ended questions included in a survey administered in January 2021 to 464 respondents living in London, during the COVID-19 lockdown. The range of impacts in the actual scenario varied from no effect on task execution, to disruption, distraction, concern of disturbing others or being heard. Positive impacts included support of concentration, relaxation, motivation, freedom of sound expression, feeling of being connected to the surroundings and comforted by the presence of others, according to mechanisms described in the study. Negative appraisal could trigger coping strategies (e.g., controlling windows, playing music, wearing headphones) and behavioural changes (e.g., lowering the volume of the voice or music, muting oneself during call, changing workout type) that could in turn limit or enhance the freedom of behaviour, affect or foster wellbeing. Negative impacts were most frequently reported on WFH (by 55% of the participants), followed by relaxation activities (40.6%), sexual activities (30.1%), and home workout (20.1%). The ideal soundscape was described as a quiet, well-sound insulated environment, which guarantees access to positive sounds (i.e., natural sounds, music, urban background), thus resulting in privacy, intimacy, and a place where to express themselves without noise-related constraints. The study complements literature findings on housing design directions in light of the COVID-19 pandemic, by providing further evidence on the impacts of poor sound insulation at home, the potential benefits of nature-based solutions for positive indoor soundscapes, and opportunities for an activity-based design of domestic environments, inclusive of a broader set of home uses and household compositions.